2019
DOI: 10.4317/medoral.22782
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene instructions and professional control as part of the treatment of desquamative gingivitis. Systematic review

Abstract: Background The aim of this present article was to evaluate the scientific evidence on the efficacy of daily hygiene and professional prophylaxis for treatment of desquamative gingivitis. Material and Methods The present systematic review was conducted following the PRISMA protocol. Searches were carried out in Pubmed, Embase, Web of Science and Cochrane Library up to July 2018, randomized clinical trials and cohort studies on desquamative gingivitis (DG), and oral disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…In this case report, patient's DG condition had improved following completion of initial periodontal therapy. This was in line with the observation [5] which had shown that reduction in the overall inflammatory condition of the mucosa, including ordinary plaque-associated inflammation, was beneficial for controlling this group of immune disease.…”
Section: Discussionsupporting
confidence: 90%
“…In this case report, patient's DG condition had improved following completion of initial periodontal therapy. This was in line with the observation [5] which had shown that reduction in the overall inflammatory condition of the mucosa, including ordinary plaque-associated inflammation, was beneficial for controlling this group of immune disease.…”
Section: Discussionsupporting
confidence: 90%
“…Los pacientes con DG deben recibir instrucciones por parte del periodoncista sobre el mantenimiento de una higiene adecuada, utilizando diferentes técnicas, cepillos de dientes con cerdas suaves o extra suaves, que se puedan insertar fácilmente sobre el surco gingival y el uso de hilo dental. 25…”
Section: Discussionunclassified
“…Another manifestation of the periodontal diseases in molar-premolar teeth is the formation of furcation defects [8][9][10][11]. Since gingivitis affects only the soft tissue, its diagnosis and treatment rely solely on clinical findings including redness, puffiness, and bleeding [12][13][14]. However, periodontitis could lead to bone additional information of clinical relevance has to be explored and evaluated.…”
Section: Introductionmentioning
confidence: 99%